Pengaruh Gaya Mengajar Latihan Terhadap Gerak Dasar Pada Servis Panjang Dalam Permainan Bulutangkis Pada Siswa SMP Negeri 2 Tondano - Cornelia Saeran; Agustinus Refly Jeffry Sengkey; Djajaty Mariana Lolowang (STIKES Columbia Asia Medan, 2024)
The problem of this research is whether the application of a training teaching style has an influence on improving basic movement skills in the badminton long serve of students at SMP Negeri 2 Tondano? This research aims to find out whether the training teaching style has the greatest influence on basic movement skills in the badminton long serve of students at SMP Negeri 2 Tondano. The research method used was an experiment using a sample of 20 students consisting of 2 groups consisting of 10 experimental groups and 10 control groups who were not given treatment. Determining groups using ordinal match pairing. The research design used was pre test post test control group design. The research was carried out 6 times face to face using basic movement skills test instruments in badminton. This instrument was created by the researcher himself, where this test was declared valid (content validity) by the supervisors, and was used to collect pre-test and post-test data for both groups. The research hypothesis being tested is that the application of a training teaching style has an influence on improving basic movement skills in the badminton long serve of students at SMP Negeri 2 Tondano. Hypothesis testing uses t test statistics at the significance level α = 0.05. The conclusion obtained from this research is that the training teaching style has an influence on improving basic movement skills in the badminton long serve of students at SMP Negeri 2 Tondano.